Exo70 subunit of the exocyst complex is involved in adhesion-dependent trafficking of caveolin-1. - Maud Hertzog (Public Library of Science (PLoS), 2012)
Caveolae are specialized domains of the plasma membrane, which play key roles in signaling, endocytosis and mechanosensing. Using total internal reflection fluorescent microscopy (TIRF-M), we observe that the exocyst subunit Exo70 forms punctuate structures at the plasma membrane and partially localizes with caveolin-1, the main component of caveolae. Upon cell detachment, we found that Exo70 accumulates with caveolin-1-positive vesicular structures. Upon cell re-adhesion, caveolin-1 traffics back to the plasma membrane in a multistep process involving microtubules and actin cytoskeleton. In addition, silencing of Exo70 redirects caveolin-1 to focal adhesions identified by markers such as α5 integrin or vinculin. Based on these findings, we conclude that Exo70 is involved in caveolin-1 recycling to the plasma membrane during re-adhesion of the cells to the substratum.